Web Genially Gamification: Development of Joyful Learning Media to Improve Literacy and Numeracy Learning Outcomes of Elementary School Students - Radeni Sukma Indra Dewi; Shirly Rizki Kusumaningrum; Siti Faizah; Intan Sari Rufiana; Maria Kurniati Jemeo; Navik Khusniah; Fahrany Wahyu Andini; Kholidatul Khasanah; Amaliya Islami Nurlaili; Megania Herawati (Universitas Nusantara PGRI Kediri, 2026)
This study aims to develop Genially Web-based Gamification learning media within the framework of Joyful Learning to improve elementary school students' literacy and numeracy learning outcomes. The method used is Research and Development (R&D) with the Lee & Owens model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation was carried out by subject matter experts and media experts, while practicality was tested by teachers and students. Effectiveness was tested through a one-group pretest and post-test design. The results showed that the Genially-based learning media obtained a highly valid rating from subject matter experts (88.33%) and media experts (82.5%). The practicality test received a very good response from teachers (90%) and students (97.39%). In addition, students’ learning outcomes in both literacy and numeracy domains showed a significant improvement. The average literacy score increased from 68.12 (pretest) to 88.74 (post-test), while the numeracy score increased from 66.22 to 89.38, resulting in an overall average N-Gain of 0.667 (medium–high category). These findings confirm that the integration of gamification through Web Genially creates a fun, interactive, and effective learning experience that simultaneously strengthens literacy comprehension and numeracy problem-solving skills among elementary school students.